The Ubiquitin Proteasome System and Nutrient Stress Response - Mackinnon, Erin; Stone, Sophia L. (Frontiers in Plant Science, 2022)
Plants utilize different molecular mechanisms, including the Ubiquitin Proteasome System (UPS) that facilitates changes to the proteome, to mitigate the impact of abiotic stresses on growth and development. The UPS encompasses the ubiquitination of selected substrates followed by the proteasomal degradation of the modified proteins. Ubiquitin ligases, or E3s, are central to the UPS as they govern specificity and facilitate the attachment of one or more ubiquitin molecules to the substrate protein. From recent studies, the UPS has emerged as an important regulator of the uptake and translocation of essential macronutrients and micronutrients. In this review, we discuss select E3s that are involved in regulating nutrient uptake and responses to stress conditions, including limited or excess levels of nitrogen, phosphorus, iron, and copper.